Kopitiam owner's perceptions towards information technology adoption / Salmalina Salleh, Norhayati Mat Yusoff @ Mohd Yusof and Dahlan Abdullah - Salleh, Salmalina; Mat Yusoff @ Mohd Yusof, Norhayati; Abdullah, Dahlan (Research Management Institute (RMI), 2012)
Technology, particularly information technology (IT), is becoming an important strategic asset for hospitality organizations such as restaurant industry to improve their organizational performance and strategic competitiveness. In general, restaurant service processes such as making reservations and ordering require waiters to record customer orders manually by using paper and pen and then transmit the order to the kitchen for preparation. Even though this procedure is very simple, it may significantly increase the workload of waiters and even cause errors in meal ordering especially during peak hour. By looking at these practices, using advance IT to improve service quality has received much attention in recent years. Therefore, the owner of the restaurants began to realize that in attempt to be competitive and improve customer satisfaction, the successful implementation of IT has undoubtedly emerged as a method maintaining the organizational performance and profitability. However, the interest to probe restaurant employee individual perceptions towards IT adoption is limited. In line with this notion the purpose of this study is to determine the restaurant employee individual perceptions towards adoption of IT. In addition, this study seeks to find out what type of IT that used in kopitiam. In obtaining the information of the topic of interest, quantitative approach through questionnaire survey with restaurant employee will be undertaken. Sample populations of this study will be among employees who work in 'kopitiam' in the Penang state that have adopted information technology. The study revealed that majority of the employee's perceives that IT adoption in their 'kopitiam' operation has made them easier and convenience.